Risk Factors for Preterm Labor in Pregnant Women from Ciego de Ávila Municipality - Silvia Estelbina Retureta Milán; Lainys María Rojas Álvarez; Marta Estelbina Retureta Milán (Medisur)
Background: according to records from the municipal health department, in Ciego de Ávila municipality, 65 children died between 2007 and 2012; 35 of them were born prematurely, indicating that preterm labor and birth is still a pending problem. Objective: to identify risk factors associated with preterm labor in Ciego de Ávila municipality. Methods: a case-control study was conducted in the municipality of Ciego de Ávila to analyze the risk factors associated with preterm labor in the period 2009-2012. The study variables were: maternal age and risk factors for preterm labor. The point estimate for the association was obtained through the odds ratio. Additionally, the Chi-square test was applied, considering that the association was significant at P<0.05. Results: the factors most associated with preterm labor were history of preterm delivery and previous abortion, low maternal weight at the first prenatal visit, height less than 150 cm, poor or excessive weight gain during pregnancy, smoking, vaginal and urinary infections, multiple gestations and uterine conditions. Conclusion: previous abortions and multiple gestations were the risk factors most frequently associated with preterm labor; however, it can be said that this problem is multifactorial in origin, not only due to the existence of other significant factors, but also because of the interrelationship between them.